Impact of falls on depressive symptoms among the oldest old: Results from the AgeQualiDe study. (19th July 2018) - Hajek, André; Brettschneider, Christian; van den Bussche, Hendrik; Lühmann, Dagmar; Oey, Anke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Stein, Janine; Luck, Tobias; et al.
Abstract : Objective: The purpose of this study was to examine the impact of falls on depressive symptoms among the oldest old in Germany longitudinally. Methods: Data were used from 2 waves of the multicenter prospective cohort "Study on needs, health service use, costs and health‐related quality of life in a large sample of oldest‐old primary care patients (85+)" (AgeQualiDe). This study covers primary care patients ≥85 years (at baseline: n = 547, average age of 88.9 ± 3.0 years; ranging from 85 to 100 years). General practitioner‐diagnosed falls were used as explanatory variable. The Geriatric Depression Scale was used as outcome measure. Results: Linear fixed effects regressions showed that the occurrence of falls is associated with an increase in depressive symptoms ( β  = .60, P  = .02), whereas changes in marital status, ageing, social support, functional decline (instrumental activity of daily living), cognitive impairment, and an increase in chronic diseases did not affect depressive symptoms. In sensitivity analysis, an increase in depressive symptoms was associated with functional impairment (basic activities of daily living; Barthel index; β  = −.04, P  = .005). Conclusions: Based on a large, population‐based longitudinal study, this study underlined the impact of falls on depressive symptoms and consequently extended previous knowledge about an association between falls and depressive symptoms in the oldest old. Developing strategies to prevent falls might also help to prevent depressive symptoms.